Innovation lowfat EBELABON from chicken egg for weight loss diet overweight students - Fitsyal Febriyadin; Anik Lestari; Sapja Anantanyu (AcTion: Aceh Nutrition Journal, 2024)
Overweight is the initial cause of degenerative diseases in the future. The purpose of this study was to determine the effect of a low-fat chicken egg-shredded innovation intervention (EBELABON) on changes in the body weight of overweight students at the Faculty of Health Sciences UMS Surakarta on weight loss. Pre-post group sampling using an experimental research approach. For 14 days, 37 FIK UMS students who met the restriction criteria were included as research participants. They were fed low-fat shredded chicken eggs (EBELABON) twice a day, in the morning (06.00-09.00) and at night (17.00-19.00). Anthropometric measurements using (BIA) and SQ-FFQ were used to obtain data. The results of data analysis using the Paired T-Test showed that the provision of low-fat EBELABON decreased body weight by 2,39 kg, body fat by 2,45%, and nutritional status by 0,94, which was significant (p <0,05) along with nutritional consultation, and there was no difference in the average difference between each treatment group and the provision of low-fat BELABON (p>0,05) using the one-way ANOVA test. In conclusion, the consumption of low-fat BELABON has an effect on weight loss, body fat, and nutritional status in overweight students for 14 days.